Analysis of Students’ Epistemic Cognition Based on Cognitive Style in Mathematical Problem Solving - Ilmiah, Ilmiah; Cahya Mar'a Saliha Sumantri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to describe students' epistemic cognition in solving mathematical problems reviewed from field independent and field dependent cognitive styles. This study uses a qualitative approach with a descriptive type of research. The subjects of the study were two students of class X of MA Abu Amr who were selected based on the results of the GEFT (Group Embedded Figures Test) test, with one student each with a field independent and field dependent cognitive style. Data were collected through mathematical problem-solving tests and interview guidelines, and then analyzed based on epistemic cognition indicators. The results showed that students with field-independent cognitive styles tended to have epistemic cognition at the rational dominant level. In contrast, field-dependent students showed a rational-empirical level of epistemic cognition. In conclusion, cognitive style affects the way students understand, process, and justify knowledge in solving mathematical problems. These findings show that there is a difference in the level of epistemic cognition based on students' cognitive styles, which can be taken into consideration in the development of learning strategies.